Pengaruh Model Collaborative Learning Tipe Group Investigation Terhadap Hasil Belajar Kognitif Siswa - Yoga Prima Shawalda; Maskun Maskun; Syaiful M (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2019)
This study aims to determine the effect of collaborative learning model of group investigation type on cognitive learning outcomes of students in the history subjects of class X IIS 4 SMA Negeri 1 Kotagajah. The method used is the Quasi Experimental design with the data collection techniques through tests, observation, documentation, and literature. The data analysis used is quantitative analysis. Based on the results of the study, it was found that there was a significant effect of the collaborative learning model of group investigation type on the cognitive learning outcomes of students in the history subjects of class X IIS 4 with the significance level obtained the tcount= 8.38≥ ttable= (0.95) (60) = 2.00. The significance level of the influence of collaborative learning model group investigation type on students' cognitive learning outcomes is 0.66 which is considered as high catagory if it is included in the interpretation of correlation.Penelitian ini bertujuan untuk mengetahui pengaruh model Collaborative Learning tipe Group Investigation terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah Kelas X IIS 4 SMA Negeri 1 Kotagajah. Metode yang digunakan adalah metode Quasi Experimental design dengan teknik pengumpulan data melalui tes, observasi, dokumentasi, dan kepustakaan. Analisis data dengan analisis kuantitatif. Berdasarkan hasil penelitian didapatkan bahwa ada pengaruh yang signifikan dari model Collaborative Learning tipe Group Investigation terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah Kelas X IIS 4 dengan taraf signifikansi yang diperoleh ialah thitung = 8,38≥ ttable = (0,95) (60) = 2,00. Besar taraf signifikansi dari pengaruh model Collaborative Learning tipe Group Investigation terhadap hasil belajar kognitif siswa didapat 0,66 yang jika dimasukkan dalam interpretasi korelasi termasuk kategori tinggi.Kata kunci : hasil belajar, model, pengaruh